PRODUSED WATER – SOURCE OF POLLUTION OR VALUABLE RESOURCE IN THE EASTERN OIL REGION, UKRAINE - Reva, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The paper describes the problem of extracting stratal water in the oil and gas fields. The author analyzes how this water can affect the environment and its security. The article defines the main directions and factors related to the pollution of aquifers, surface water and soil stratal waters. The purpose of the study is to investigate the basic components and chemical compounds which are dissolved in produced water and cause the pollution. The paper analyzes the environmental problems which were caused as a result of discharge, infiltration and storage of water reservoir. Examples of pollution of stratal waters which were pre-cleaned before discharging are also described. These problems are taken and described on the basis of Ukrainian and international experience. These examples show that the issue of environmental pollution is important for Ukrainian oil and gas geology in eastern oil region (the Dnieper-Donets basin. We investigated the problems, which occurs after entering of the water reservoir into other geological and ecological systems. This causes the disturbance of natural equilibrium and further raises a number of other problems. The author highlights the main problems – pollution of aquifers exploited for drinking and household water supply, pollution of surface waters, and salinization of fertile agriculture soils. These issues are very relevant because the land and water using is more important than the oil and gas extraction. The monitoring for the determination of the chemical elements and contained compounds in reservoir water at the early stages of development and directly during the operation is proposed. This will simplify the selection of the methods for operational localization of the pollution and methods for purification of produced water. General information about the content of such components as Br, B, I, Li and others in the extracted water gives the possibility to consideration this raw material for production.
Keywords: environment; infiltration; pollution; produced water; salinity; stratal water